TO THE QUESTION OF THE ASSESSMENT OF LOCUSES SQUAMOUS EPITHELIALIZATION AFTER SURGICAL CORRECTION OF THE BARRETT’S ESOPHAGUS - G. M. Mogilnaja; V. M. Durleshter; V. L. Mogilnaja; L. G. Drjaeva (Медицинский вестник Юга России, 2014)
Purpose: To evaluate the squamous epithelialization in Barrett’s esophageal mucosa after forming arefluх cardia.Materials and Methods: A dynamical endoscopical examination of 47 patients with Barrett’s esophagus after forming arefluх cardia followed by taken biopsies for morfohistochemical and immunohistochemical study.Results: After surgical treatment in the mucosa of Barrett’s esophagus foci of squamous epithelialization are formed.Summary: Formed areflux cardia prevents reflux of acidic stomach contents into the esophagus, that contributes the regeneration and epithelialization of the mucosa.